2013
DOI: 10.3892/ijmm.2013.1368
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cardiac inflammation and remodeling during the development of streptozotocin-induced diabetic cardiomyopathy in vivo: A time course analysis

Abstract: In this study, we examined cardiac inflammation, fibrosis and left ventricular (LV) function during the development of streptozotocin (STZ)-induced diabetic cardiomyopathy using an animal model of diabetes mellitus (DM). Diabetes was induced in 22 Sprague‑Dawley rats by an intraperitoneal single injection of STZ (70 mg/kg). Non-diabetic animals served as the controls (n=6). LV function was documented using the conductance catheter technique 2 and 6 weeks after the induction of diabetes. Cardiac tissue was anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 30 publications
(34 reference statements)
3
21
0
3
Order By: Relevance
“…Becher et al, using a Sprague-Dawley STZ-DM model (single STZ [70 mg/kg] injection) and using the conductance Millar catheter technique, found significant changes in left ventricular relaxation that occurred at 2 weeks post STZ injection. Impaired relaxation was exemplified by increases in left ventricular diastolic relaxation time (msec) and decreases in left ventricular diastolic relaxation (mm Hg/sec), these changes were also found in conjunction with decreases in cardiac output and decreased left ventricular contractility (mm Hg/sec), indicating reduced systolic function [33]. Changes in cardiac structure, such as cardiac dilation were evident at 4 weeks, exemplified by increased left ventricular end diastolic and systolic dimensions and decreases in relative wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Becher et al, using a Sprague-Dawley STZ-DM model (single STZ [70 mg/kg] injection) and using the conductance Millar catheter technique, found significant changes in left ventricular relaxation that occurred at 2 weeks post STZ injection. Impaired relaxation was exemplified by increases in left ventricular diastolic relaxation time (msec) and decreases in left ventricular diastolic relaxation (mm Hg/sec), these changes were also found in conjunction with decreases in cardiac output and decreased left ventricular contractility (mm Hg/sec), indicating reduced systolic function [33]. Changes in cardiac structure, such as cardiac dilation were evident at 4 weeks, exemplified by increased left ventricular end diastolic and systolic dimensions and decreases in relative wall thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Using mouse or rat models of type I diabetes they also demonstrated that neutralization of TNFα [120] or genetic deletion of kinin receptor B [121] attenuated the development of experimental diabetic cardiomyopathy associated with a reduction of intramyocardial inflammation and cardiac fibrosis. They also showed that inhibition of p38 mitogen-activated protein kinase attenuated left ventricular dysfunction by decreasing the level of myocardial pro-inflammatory cardiac cytokines in a mouse model of diabetes mellitus[122], and more recently they suggested that the STZ-induced diabetic cardiomyopathy is a robust model for investigating cardiac immune response and LV remodeling processes under diabetic conditions [123]. Several studies from other groups have also found similar pro-inflammatory changes in the myocardium of diabetic rodent hearts [37, 38, 41].…”
Section: Inflammation In Diabetic Cardiomyopathymentioning
confidence: 99%
“…Although different mechanisms have been proposed for the development of the diabetic cardiomyopathy (DCM) phenotype, most available data suggest that cellular oxidative stress and moderate inflammation constitute early cardiac responses to hyperglycemia and associated metabolic alterations [2,3,4]. …”
Section: Introductionmentioning
confidence: 99%